Implementation of the independent learning concept in understanding contemporary and controversial history in Indonesia and Malaysia - Suwirta Suwirta; Nana Supriatna; Ismail Ali (Minda Masagi Suci Foundation and ASPENSI, 2022)
Learning History in schools requires new paradigms and practices that enable history teachers and students studying History to have creative and imaginative thinking skills. This article–using a qualitative approach and analytical-descriptive explanation, as well as the results of literature reading, field observations, and FGD (Focus Group Discussion) with History teachers from Indonesia and Malaysia–examines Creative Pedagogy, an art of teaching which offers new perspectives and ways to develop the ability of educators and students involved in History Education to get used to "divergent" thinking. This skill is especially useful in understanding key concepts in the discipline of History, namely: Facts and Interpretation; Evidence and Causality; and Text and Context. The process of learning History, dealing with contemporary events and controversial issues in History Textbooks for Secondary Schools, must free educators and participants from the confines of an uncreative tradition. Finally, the ability to remember and memorize must be accompanied and developed with creative imagination and elaboration abilities, and must be taken into assessment of the process and results of History learning.